Parental, Prenatal, and Neonatal Associations With Ball Skills at Age 8 Using an Exposome Approach. (October 2014) - Golding, Jean; Gregory, Steven; Iles-Caven, Yasmin; Lingam, Raghu; Davis, John M.; Emmett, Pauline; Steer, Colin D.; Hibbeln, Joseph R.
There is little consistency in the literature concerning factors that influence motor coordination in children. A hypothesis-free "exposome" approach was used with 7359 children using longitudinal information covering 3 generations in regard to throwing a ball accurately at age 7 years. The analyses showed an independent robust negative association with mother's unhappiness in her midchildhood (6-11 years). No such association was present for study fathers. The offspring of parents who described themselves as having poor eyesight had poorer ability. This hypothesis-free approach has identified a strong negative association with an unhappy childhood. Future studies of this cohort will be used to determine whether the mechanism is manifest through differing parenting skills, or a biological mechanism reflecting epigenetic effects.